The rag and bone shop - Cormier, Robert (New York, N.Y. : Delacorte Press, 2001)
Trent, an ace interrogator from Vermont, works to procure a confession from an introverted twelve-year-old accused of murdering his seven-year-old friend in Monument, Massachusetts.
730
Accelerated Reader AR
Keywords: Criminal investigation -- Juvenile fiction; Mystery and detective stories; Police -- Juvenile fiction; Murder -- Juvenile fiction; Massachusetts -- Juvenile fiction